A multi-centre collaborative study on the potency estimation of ReFacto - Hubbard, Anthony R.; Sands, Dawn; Sandberg, Eva; Seitz, Rainer; Barrowcliffe, Trevor W. (Thrombosis and Haemostasis, 2003)
Seven laboratories estimated factor VIII coagulant activity in recombinant B-domain-deleted (ReFacto) and plasma-derived FVIII concentrates (Octonativ-M) using chromogenic methods relative to the WHO 6th International Standard FVIII Concentrate (WHO 6th IS), European Pharmacopoeia BRP#2 (EP#2) and the ReFacto Laboratory Standard (RLS). Significantly higher estimates were obtained for all batches of product when calculated relative to the RLS in comparison with estimates vs WHO 6th IS and EP#2. Mean estimates for two batches of ReFacto product vs the RLS were within 10% of the labelled potency whereas estimates vs WHO 6th IS and EP#2 ranged from 21 to 31% lower than the label. Conversely, mean estimates for Octonativ-M relative to WHO 6th IS and EP#2 were within 10% of the label whereas the mean estimate vs RLS was 117% of label. Mean estimates for the ReFacto product, vs the WHO 6th IS and EP#2, varied considerably between the different chromogenic kits whereas estimates vs the RLS showed good agreement between kits. Mean estimates for the RLS vs the WHO 6th IS (8.10 IU/vial) and the EP#2 (7.66 IU/vial) were lower than the assigned value of 9.4 IU/vial. The results are consistent with ReFacto and full-length FVIII responding differently to variations in assay methodology and also indicate that the assigned value on the RLS may be too high. Since this study the unitage on the RLS has been adjusted to effectively increase the amount of ReFacto in the product by 20%.
Keywords: Factor VIII; Haemophilia A; chromogenic assays